Problematika Pembacaan Al-Qur’an dengan Nagham/Langgam Jawa dalam Wacana Islam Nusantara - Zunita Lut Fiana Pangesti; Salamah Noorhidayati; Kojin Kojin; Ahmad Zainal Abidin; Melati Almatu Sholikah (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to provide a comprehensive perspective on the use of Javanese nagham in reciting the Qur'an. Scholars have debated this issue, and the purpose of this research is to analyze their views, conduct historical exploration, and understand the cultural context to establish a basis for critical thinking about the legal aspects of using Javanese nagham or langgam. Additionally, this research seeks to explore the implications that arise from this issue. The research methodology employed is qualitative, and data were collected through library research using descriptive-analytical methods. The study focuses on the differing perspectives of scholars regarding the use of Javanese nagham in Qur'anic recitation and its implications for the discourse of Nusantara Islam. The study reveals that scholars' opinions on the use of Javanese langgam in Qur'anic recitation are divided into three categories. The first category consists of scholars who support the use of Javanese style on the condition of adhering to the rules of tajwid. The second category comprises scholars who oppose the use of Javanese style, arguing that the Qur'an should be preserved from influences other than the Arabic nagham. The third category comprises moderate scholars who allow the use of any style as long as it adheres to the rules of tajwid. The implications of using Javanese nagham on the discourse of Nusantara Islam create conflicts between preserving cultural identity and religious conservation, differences in recitation patterns of the Qur'an and tajwid rules, and bring forth possible solutions to widely accept Javanese langgam recitation by the community. In conclusion, this study provides a comprehensive perspective on the use of Javanese nagham in reciting the Qur'an and its implications for the discourse of Nusantara Islam. The study highlights the differing perspectives of scholars and offers possible solutions to the conflicts arising from the use of Javanese style.